Creating Value Through IPOs - Binnamangala Anjanappa, Sahana (2012)
Despite there being many studies done in IPOs, there are many unknown still exists about the inner working of an IPO process. This paper concentrates to find the value of a company through its IPO. However the study is not in financial terms. The study concentrates on three factors of an IPO that may help a company be valued by it. The first is the Security and Exchange Commission (SEC) approval with as less a glitch as possible. The second is the underwriter, how he handles a company during the IPO (this also includes the management). Lastly is how the pricing of an IPO affects the company. The study also concentrates on the other factors in the IPO such as the timing of the IPO, reputation of the company etcetera, but not in depth. The results obtained from this study is not concrete but more of an observation.